CT Myelography for the Planning and Guidance of Targeted Epidural Blood Patches in Patients with Persistent Spinal CSF Leakage - Wendl, C.M. (AJNR Am J Neuroradiol, 2012)
Intracranial hypotension is a rare cause of persistent headache mostly originating from a dural CSF leak. If a conservative treatment fails, a minimally invasive EBP can lead to a successful sealing of such a leak. Independent of the leakage site, an EBP is usually applied at the lumbar level with varying success. We used CT myelography to detect the site of the dural leakage, then immediately applied a targeted EBP at the corresponding level to patch the leak. Seven patients from our clinic were treated with a single targeted EBP in the lumbar or cervical spine. Within 24 hours, 6 patients experienced a considerable relief of symptoms; 1 patient went into remission after a repeat procedure. Our preliminary data suggest that a CT-guided, CT myelography-assisted targeted EBP is a safe and effective treatment for persistent spinal CSF leaks.